Usefulness of second 131I treatment in biochemical persistent differentiated thyroid cancer patients - Carla Gambale; Alessandro Prete; Lea Contartese; Liborio Torregrossa; Francesca Bianchi; Eleonora Molinaro; Gabriele Materazzi; Rossella Elisei; Antonio Matrone (European Thyroid Journal, 2023)
Background: Second 131I treatment is commonly performed in clinical practice in patients with differentiated thyroid cancer and biochemical incomplete or indeterminate response (BiR/InR) after initial treatment. Objective: The objective of the is study is to evaluate the clinical impact of the second 131I treatment in BiR/InR patients and analyze the predictive factors for structural incomplete response (SiR). Patients and methods: One hundred fifty-three BiR/InR patients after initial treatment who received a second 131I treatment were included in the study. The clinical response in a short- and medium- long-term follow-up was evaluated. Results: After the second 131I treatment (median 8 months), 11.8% patients showed excellent response (ER), 17% SiR, while BiR/InR persisted in 71.2%. Less than half (38.5%) of SiR patients had radioiodine-avid metastases. Patients who, following the second 131I treatment, experienced SiR had larger tumor size and more frequently aggressive histology and vascular invasion than those experienced BiR/InR and ER. Also, the median values of thyroglobulin on levothyroxine therapy (LT4-Tg), Tg peak after recombinant human TSH stimulation (rhTSH-Tg) and thyroglobulin antibodies (TgAb) were significantly higher in patients who developed SiR. At last evaluation (median: 9.9 years), BiR/ InR persisted in 57.5%, while 26.2% and 16.3% of the patients showed ER and SiR, respectively. About half of BiR/InR patients (71/153 (46.4%)) received further treatments after the second 131I treatment. Conclusions: Radioiodine-avid metastatic disease detected by the second 131I is an infrequent finding in patients with BiR/InR after initial treatment. However, specific pathologic and biochemical features allow to better identify those cases with higher probability of developing SiR, thus improving the clinical effectiveness of performing a second 131I treatment.